SYNTHESIS OF TITANIUM DIOKSIDA (TiO2) FILM WITH SPHERICAL THREE DIMENSIONAL STRUCTURE ON FLUORINE TIN OXIDE (FTO) SUBSTRATE USING SOLVOTERMAL METHOD FOR CARBON MONOXIDE GAS SENSOR APPLICATION - SYUHADA (NIM : 23315306), NURNADIYAH
Air pollution nowdays has become serious problem that must be solved immediately. One of them is carbon monoxide pollution. Carbon monoxide gases known as harmfull gases toward human health because when it exposed to the body, the blood loses its ability to bind oxygen. Furthermore, due to its odorless and invisible, carbon monoxide gases can be accidentally inhaled. Therefore, an early detector of the presence of carbon monoxide gases is needed. This research has successfully investigated the performance of titanium dioksida material for detection the carbon monoxide gas. The concentration of carbon monoxide gas that used is 100 ppm. The titanium dioksida material was synthesis using solvotermal method at 180 oC with different reaction times. The substrate that used is fluorine tin oxide (FTO, this substrate was placed inside Teflon lined 100 ml autoclave at horizontal position with the FTO layer facing upwads. The final result obtained is white titanium dioksida layer with well uniformly distributed. Then, the film was heated at 550 oC for 6 hours to remove the residual reaction. The silver electrode was deposition using doctor blade technique. The solvotermal reaction time in this study were 6 hours, 12 hours, 20 hours, and 36 hours. These samples were characterization using x-ray diffraction (XRD), Scanning elektron microscopy (SEM), Energy Dispersive Spectroscopy, Brunnauer-Emmett-Teller (BET) and carbon monoxide as gas sensor testing. The XRD results show that the materials were synthesized was titanium dioksida with a rutile crystal phase. The SEM results show that the titanium dioksida formed is a spherical three-dimensional or round structure with covered by nanorods TiO2. The diameter size of microsphere and the nanorods diameter increases with the enhanced of the solvotermal reaction time. The diameter size of microsphere respectively for samples of 6 hours, 12 hours, 20 hours and 24 hours were 2.5 Ã‚Âµm, 4 Ã‚Âµm, 5 Ã‚Âµm, 5 μm and the nanorods size were 21 nm, 38 nm, 42 nm, 53 nm. The SEM morphology indicates that the samples were uniformly. EDS results show that the ratio of Ti : O is 35:65. The BET results show the specific surface area of TiO2 sample 12 hours and TiO2 6 hours is 21.336 and 20.537 m2/g and m2/g. It indicates that when the solvotermal reaction time increases, the specific surface area of the material also increases. Titanium dioksida materials that was prepared with different Hidrotermal reaction times can be used as carbon monoxide gas sensors. The testing of Sensor using temperatur from 150 oC to 350 oC with 100 ppm concentration CO gas for exposure time 10 minutes. The sensor test results show that the best response that was obtained is 24.7% from sample TiO2 12 hours at 350 oC temperatur. Beside that the sample also testing with CO gas at different concentrations ie 25 ppm, 50 ppm, 75 ppm, 90 ppm and 110 ppm.